Personalized English Online Assessments to Improve Students Engagement Based on Learning Oriented Approach (An Action Research) - Rahmayani; Tjalla, Magdahalena; Arqam; Haris Sunubi, Abd.; Zulfa (Tarling : Journal of Language Education, 2024)
Problems related to the assessment such as technical issues, attitude toward the assessment, honesty, and participation, became highlight issues in researcher’s online classroom. The researcher experienced that there seemed a tendency where the previous assessments were only required to achieve the minimum completeness criteria with less regard to the learning engagement, impression as well as the value of learning. This research used an action research as the design. For data collection, the researcher obtained them through deep interview to the students, continues observation, as well as students assessment result in all cycles. The data analysis technique used a simple statistical data analyses for students assessment result, and domain analysis for interview and observation. The finding of the research showed that the personalized online learning assessment administered by the researcher was focusing on how the assessment brought impact to the students learning. The personalization was done in three classroom segments; pre, while, and post class, with two cycles. It was concluded that the personalization had given impressions on students’ learning engagement. As the result, it could be seen that the assessment had given a significant improvement to their learning outcomes; either to their daily test, classroom participations, as well as motivation.